Medication persistence in older women with osteoporosis: a pilot study. Issue 12 (December 2015) - Gillette, C.; Howerton, D.; Williams, B.; Mahmood, M.
Abstract Summary Most osteoporosis patients stop their medications before they should. Side effects are the most common reason patients in this sample stopped their medication before they told their physician. Physicians should use shared decision-making and discuss side effects of osteoporosis medications with their patients and explain the risks of the medications. Introduction The aims of this study were to (a) qualitatively examine reasons for medication non-persistence in osteoporosis, and (b) investigate how medication non-persistence in osteoporosis is associated with outcome expectations, self-efficacy, trust in physicians, and health locus of control. Methods Subjects were recruited from online support groups to answer an anonymous online survey. Subjects were eligible if they (a) were female, (b) were at least 40 years of age, (c) self-identify as having osteoporosis, and (d) have taken at least one medication for osteoporosis. During the survey, subjects completed measures of self-efficacy, outcome expectations, trust in physicians generally, health locus of control, and demographic information. Results Thirty-four subjects completed the online survey and had usable data. Approximately 82 % (n  = 28) of subjects reported discontinuing an osteoporosis medication without first consulting a physician. The most common reason patients discontinued an osteoporosis medication was adverse effects. Subjects were more likely to discontinue their medications when they had poorer outcome expectations on average (p  = 0.01), had lower trust in physicians on average (p  < 0.0001), and had more of a doctors-centered locus of control (p  = 0.03). Self-efficacy, age, insurance, status, and other measures of locus of control were not associated with medication non-persistence. Conclusions Side effects are a significant concern for women with osteoporosis and may be a cause for medication non-persistence.